2019
DOI: 10.1111/opo.12646
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of an electronic head‐mounted low vision aid

Abstract: Purpose To evaluate the efficacy of electronic head‐mounted low vision aid (e‐LVA) SightPlus (GiveVision, UK, givevision.net) and to determine which people with low vision would see themselves likely using an e‐LVA like this. Methods Sixty participants with low vision aged 18 to 93 used SightPlus during an in‐clinic study session based on a mixed methods design. Visual acuity (ETDRS), contrast sensitivity (Pelli‐Robson) and reading performance (MNREAD) were measured binocularly at baseline (no device), with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 22 publications
2
42
1
Order By: Relevance
“…Recent advances in technology have led to the availability of smaller, lighter, and more versatile electronic head-mounted LVA 12 , 13 . However, to date, only one study has reported the clinical benefit of a smartphone-based head-mounted LVA in clinical settings (SightPlus®) 14 . SightPlus included five pre-set image enhancement modes, and the study found improvements in distant and near visual acuities and contrast sensitivity in 60 patients with visual impairment 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in technology have led to the availability of smaller, lighter, and more versatile electronic head-mounted LVA 12 , 13 . However, to date, only one study has reported the clinical benefit of a smartphone-based head-mounted LVA in clinical settings (SightPlus®) 14 . SightPlus included five pre-set image enhancement modes, and the study found improvements in distant and near visual acuities and contrast sensitivity in 60 patients with visual impairment 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Globally, approximately 216 million people live with moderate to severe visual impairment ( Bourne, Flaxman, Braithwaite, Cicinelli, Das, Jonas, et al, 2017 ), with these numbers predicted to rise over coming decades due to an aging population ( Access Economics Pty Ltd, 2009 ; Pezzullo, Streatfeild, Simkiss, & Shickle, 2018 ). Although for many people sight loss cannot be reversed or cured, low vision aids (LVAs) can have a positive impact on residual functional sight ( Crossland, Starke, Imielski, Wolffsohn, & Webster, 2019 ; Binns, Bunce, Dickinson, Harper, Tudor-Edwards, Woodhouse, et al, 2012 ; Hooper, Jutai, Strong, & Russell-Minda, 2008 ; Peterson, Wolffsohn, Rubinstein, & Lowe, 2003 ; Virgili, Acosta, Bentley, Giacomelli, Allcock, & Evans, 2018 ), with a prominent research focus on restoring the ability to read ( Virgili et al, 2018 ). Optical low vision aids tend to be task specific, with constraints on magnification, field of view, working distance, and ease of use: stronger optical magnifiers typically have a smaller field of view, are harder to align, and are more affected by hand movement than weaker devices.…”
Section: Introductionmentioning
confidence: 99%
“…The questions specifically developed for this study about device user's characteristics and changes in use identified that the activities for which eSight device was most used were as follows: reading and watching TV (see Appendix, available at http://links.lww.com/OPX/A493 , for detailed individual goals), a finding that is consistent with other studies on head-mounted display systems. 7 , 32 Those who reported nonuse of the device were those for which these activities were the least performed with the eSight. The activities for which the device was least used included cooking, shopping, and meetings.…”
Section: Resultsmentioning
confidence: 99%